Strategy decision of business interruption insurance and emergency supply strategy based on supply disruptions - Xinjun Li; Lijie Wang (Journal of Industrial Engineering and Management, 2015)
Purpose: Recent years have witness the pervasive supply disruptions and their impacts on supply chain performance. It is significant for enterprises to adopt comprehensive measures to cope with supply disruptions. The purpose of this study is to investigate how BI insurance make up the shortage of emergency supply and affect the expected profit of enterprises. Design/methodology: This study develops the penalty cost function on the basic of the financial costs caused by the interruption losses, introduces variables of BI insurance and operational measures, establishes the profit model with BI insurance or not. Findings: Through the proof and analysis, it is demonstrated that BI insurance can mitigate the adverse effect of the increasing cost for expected profit. And this study finds that the value of BI insurance is higher when interruption probability is lower and penalty coefficient is higher. Originality/value: In this study, it is investigated that the impact of business interruption (BI) insurance on supply disruptions and its complementary value against the higher purchase cost of emergency sourcing strategy. BI insurance is an efficient measure for supply interruption and should be adopted correctly to play a role in managing supply disruption risk.